Perencanaan Persediaan Suku Cadang Dengan Metode Economic Order Quantity (EOQ) Single Order Multiple Product Di PT. ABCD - Gusti Rahmatullah; Johan K. Runtuk (President University, 2020)
Spare parts are an important factor in the continuity of the production process for a manufacturing company. Its existence affects the company's operational processes. Besides, the inventory cost requires a large enough capital from the company's total capital. PT. ABCD currently has not applied the ABC method to determine the category of each part. This research was conducted by analyzing nine critical parts obtained from the ABC analysis results for the fast-moving category. The parts analyzed were focused on category A, with a fast-moving part value of 80.71% of the total existing parts. Based on Period Order Quantity (POQ) method, it was found that the total inventory cost applied by the company for the nine types of critical parts was IDR 37,054,735. In contrast, using the Economic Order Quantity (EOQ) method single order multiple products resulted in a total inventory cost of IDR 18 841,277, -. This result is better than the method established by the company, with savings of Rp. 18,213,458,